Total Knee Arthroplasty for Contractures in Patients with Rheumatoid Arthritis - Herasymenko, S.I.; Poluliakh, M.V.; Babko, A.M.; Herasymenko, A.S.; Poluliakh, D.M.; Kachan, D.I.; Kostohryz, Yu.O.; Duda, M.S.; Huzhevskyi, I.V. (TERRA ORTHOPAEDICA, 2023)
Summary. Knee joint injury in patients with rheumatoid arthritis (RA) occurs in 70% of cases. This is the most common cause of loss of work capacity and the ability to selfcare; patients become severely disabled, since the disease is accompanied by contractures with the development of discordant positions of the lower limbs, which leads to a partial or complete loss of the function of support and walking. Thus, this problem needs to be studied. Objective: to analyze the orthopedic treatment of secondary arthrosis of the knee joints in patients with RA, complicated by contractures. Materials and Methods. In this study, we have analyzed the orthopedic treatment of 66 RA patients with secondary arthrosis with contractures, who underwent 75 total knee replacements between 2013 and 2020. Anamnestic data, clinical, biomechanical and statistical research methods were used. Results. The analysis of the results of total knee replacement was followed in the period from 6 months to 5 years. The results were evaluated according to the 100-point scale by J. Joseph, E.E. Kaufman (1550). The majority of patients had good treatment results. Conclusions. Total knee replacement is required in patients with 2nd phase of the stage II of the disease and higher. In our opinion, this is the most optimal time for surgical treatment, which allows patients with RA to fully use the capabilities of an implanted endoprosthesis.